LEARNING MOTIVATION AND MATHEMATICAL UNDERSTANDING OF STUDENTS OF ISLAMIC JUNIOR HIGH SCHOOL THROUGH ACTIVE KNOWLEDGE SHARING STRATEGY - Rahayu Kariadinata; R Poppy Yaniawati; Hamdan Sugilar; Dede Riyandani (IKIP Siliwangi and I-MES, 2019)
This study aims to analyze and describe learning motivation, mathematical understanding and activities of students' and teachers at Islamic Junior High School (Madrasah Tsanawiyah/MTs) through Active Knowledge Sharing strategy. The research is conducted in MTs. Al-Mukhlisin Bandung Indonesia. The method of this research is a mixed method with Classroom Action Research (CAR). The instruments used were motivation questionnaires, observation sheets, mathematical understanding tests and observation sheets. The results of the research indicate that learning motivation, mathematical understanding and activities of teachers and students through the Active Knowledge Sharing strategy increase in each cycle. Students' learning motivation is shown from the result of the questionnaire, states that the average percentage of motivation indicator increase in each cycle, those are 70,35% (cycle I), 71,17% (cycle II ) and 72.15% (cycles III), student mathematical understanding indicated from the test results states that the average value increases in each cycle and the end of the cycle has reached the classical completeness, that is 79.41%, the activities of students and teachers during teaching- learning increased in each cycle of 60.95% (cycle I), 73.33% (cycle II) and 86.67% (cycles III).